2009
DOI: 10.1159/000207448
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Paracetamol and Nefopam Antinociception by Serotonin 5-HT<sub>3</sub> Receptor Antagonists in Mice

Abstract: Background/Aims: Post-operative nausea and vomiting are common adverse events that require administration of anti-emetic compounds, such as the serotonin 5-HT3 receptor antagonists, but these drugs can also reduce the analgesic efficacy of some analgesics (paracetamol, tramadol). Methods: The present study was designed to explore the effect of 3 serotonin 5-HT3 receptor antagonists on the antinociceptive efficacy of another frequently used post-operative analgesic, nefopam, in the mouse w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…8 Hence, it has become a mainstay of many multimodal postoperative analgesia regimen, 22 but the analgesic efficacy is still debated, [9][10][11][12] especially as its pharmacokinetic is affected by other drugs used in the perioperative setting. 13 Although they may have a more pronounced risk profile, other intravenous non-opioids like dipyrone or parecoxib are frequently preferred. Indeed, dipyrone is not licensed in many countries due to potential risk of serious blood dyscrasias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Hence, it has become a mainstay of many multimodal postoperative analgesia regimen, 22 but the analgesic efficacy is still debated, [9][10][11][12] especially as its pharmacokinetic is affected by other drugs used in the perioperative setting. 13 Although they may have a more pronounced risk profile, other intravenous non-opioids like dipyrone or parecoxib are frequently preferred. Indeed, dipyrone is not licensed in many countries due to potential risk of serious blood dyscrasias.…”
Section: Discussionmentioning
confidence: 99%
“…When emesis required additional treatment by 5-HT(3)-receptor antagonists, which affect the action of paracetamol, these patients were excluded from the pain analysis. 13 The PCA devices and the use of VASs were explained to patients preoperatively. If a patient experienced insufficient pain relief (surgical VAS >40), rescue analgesia was provided as additional boluses of intravenous piritramide 2 mg until pain relief was satisfactory (VAS <40).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was, therefore, suggested that the antagonistic effect of tropisetron was mediated through a specific tropisetron-sensitive receptor [15]. In a recent study with mice, however, a high subcutaneous dose of ondansetron did attenuate the antinociceptive action of paracetamol, [16] but another study could not replicate this result [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, investigations of the involvement of 5-HT 3 receptors yielded conflicting results in both animals [36,42,43,47,49,50] and humans [51][52][53][54]. Interestingly, some of these studies showed that tropisetron, a nonspecific 5-HT 3 receptor antagonist, blocked the analgesic effect of paracetamol.…”
Section: Involvement Of the Serotonergic Systemmentioning
confidence: 99%